2017
DOI: 10.1099/jgv.0.000951
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Porcine sapelovirus in Hunan, China

Abstract: Porcine sapeloviruses (PSVs) are widely distributed in pig populations; however, little information on their evolutionary history and the mechanisms driving their divergence is available. Therefore, in the present study, 241 fecal samples and 91 intestinal contents collected from pigs at 26 farms in Hunan, China, were tested for the presence of PSVs. The overall PSV positivity rate was 46.39 %, with a particularly high infection rate detected in nursery and fattening pigs. A total of 29 PSV strains (PSV-HuNs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 47 publications
7
43
4
Order By: Relevance
“…The results of pairwise sequence comparisons between the study virus and its closest PSV-1 relative of all 12 viral peptide-encoding genome regions and different positions of SZ1M-F/PSV/HUN/2013 in the P1 and 3D phylogenetic trees may also reflect the independent origin of the P1 and P2-P3 genome regions. Recombination is relatively frequent among PSVs and a putative recombinant hotspot was identified near the 3′ end of the P1 region of PSVs [10,20], which could be the potential recombination breakpoint of SZ1M-F/PSV/HUN/2013, therefore the recombinant nature of the study PSV strain is plausible. Unfortunately, due to the lack of potential parental sequences of P1 none of the recombination detection programs (RDP4 or SimPlot) showed clear in silico evidence supporting this hypothesis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of pairwise sequence comparisons between the study virus and its closest PSV-1 relative of all 12 viral peptide-encoding genome regions and different positions of SZ1M-F/PSV/HUN/2013 in the P1 and 3D phylogenetic trees may also reflect the independent origin of the P1 and P2-P3 genome regions. Recombination is relatively frequent among PSVs and a putative recombinant hotspot was identified near the 3′ end of the P1 region of PSVs [10,20], which could be the potential recombination breakpoint of SZ1M-F/PSV/HUN/2013, therefore the recombinant nature of the study PSV strain is plausible. Unfortunately, due to the lack of potential parental sequences of P1 none of the recombination detection programs (RDP4 or SimPlot) showed clear in silico evidence supporting this hypothesis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal cleavage sites of the P1 capsid proteins of PSVs are experimentally determined [18]. The VP1 capsid protein, which contains major antigenic epitopes, is generally used for sero/genotyping of sapelovirus strains [10,[18][19][20]. Although PSVs are known to be a genetically highly diverse group of viruses, with recombination potential, only a single genotype of PSV has been identified based largely on VP1 sequence analyses [10,16,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14.3 Kumari et al 2019). A Chinese study reported the recombination hotspot near 3′ of the VP1 gene and showed six interclades within PSV recombinant strains (Yang et al 2017).…”
Section: Geographic Distribution and Strain Variabilitymentioning
confidence: 99%